"Trying to write a story together": general practitioners' perspectives on culturally sensitive care - Robin Vandecasteele; Lenzo Robijn; Peter A. J. Stevens; Sara Willems; Stéphanie De Maesschalck (BMC, 2024)
Abstract Background Culturally sensitive care is integral to effective and equitable healthcare delivery, necessitating an understanding and acknowledgment of patients' cultural needs, preferences, and expectations. This study investigates the perceptions of cultural sensitivity among general practitioners (GPs), focusing on their intentions, willingness and perceived responsibilities in providing care tailored to cultural needs. Methods In-depth interviews were conducted with 21 Flemish GPs to explore their perspectives on culturally sensitive care. Data analysis followed a conventional qualitative content analysis approach within a constructivist framework. A coding scheme was developed to identify recurring themes and patterns in the GPs' responses. Results Findings reveal that culturally sensitive care provision is perceived as a multifaceted process, initiated by an exploration phase where GPs inquire about patients' cultural needs and preferences. Two pivotal factors shaping culturally sensitive care emerged: patients' specific cultural expectations and GPs' perceived responsibilities. These factors guided the process of culturally sensitive care towards three distinct outcomes, ranging from complete adaptation to patients' cultural requirements driven by a high sense of responsibility, through negotiation and compromise, to a paternalistic approach where GPs expect patients to conform to GPs' values and expectations. Three typologies of GPs in providing culturally sensitive care were identified: genuinely culturally sensitive, surface-level culturally sensitive, and those perceiving diversity as a threat. Stereotyping and othering persist in healthcare, underscoring the importance of critical consciousness and cultural reflexivity in providing patient-centered and equitable care. Conclusions This study emphasizes the significance of empathy and underscores the necessity for GPs to embrace the exploration and acknowledgement of patients' preferences and cultural needs as integral aspects of their professional role. It highlights the importance of shared decision-making, critical consciousness, cultural desire and empathy. Understanding these nuances is essential for enhancing culturally sensitive care and mitigating healthcare disparities.